KONVERGENSI PEMBAGIAN HARTA WARIS DALAM HUKUM ISLAM - Sakirman, Sakirman (Alhurriyah, 2017)
The law of Inheritance in Islamic law as one part of the law of family (al-ahwalus al-Syahsiyah) is very important in order in execution studied Division of property inheritance does not occur the error and can be implemented with seadil-fair, because by studying the Islamic inheritance laws then for Muslims, will be able to fulfil the rights relating to inheritance after it was abandoned by the muwarris (the heiress) and delivered to the beneficiary who is entitled to receive it. Thus one can avoid Sin i.e. it takes a property which is not right, because it is not ditunaikannya the Islamic law regarding inheritance. The Division of the estate in islam has been so clearly set up in al Qur'an, in surat an-Nisa. God with all his grace, has given guidelines in directing humans in terms of Division of property inheritance. Division of property is aimed at in order to be among the people who left no quarrels in doling out the estate. The estate be shared if indeed people who died leaving the property useful for others. Rules regarding marriage and Mewaris arranged in a book of civil law Act ("KUHPerdata"), applies to the Eastern Chinese Foreign WNI, who are not Muslim. In article KUHPerdata 852 stated among other things that: the beneficiary is a child or all of their descendants, let me be born from other marriage though, mewaris from both parents, grandparent or all their blood family next in a straight line upwards with no difference between men or women and there is no difference between the birth of the first. They head for the sake of mewaris head if they died with the associated families in degrees is considered and each have the right because it yourself; They mewaris a stake for the sake of the stake, if they all or just some of them act as a replacement. In the case concerning the inheritance of a husband or wife who died first, the wife or husband who lives longest equated with a legitimate child of the deceased. Based on the foregoing means children descendants entitled to mewaris from parents or grandparents and the family of blood with the same part number. So did his wife, have the right and the magnitudes of the heritage as well as legitimate children. Hukum Kewarisan menurut hukum Islam sebagai salah satu bagian dari hukum kekeluargaan (al-ahwalus al-Syahsiyah) sangat penting dipelajari agar supaya dalam pelaksanaan pembagian harta warisan tidak terjadi kesalahan dan dapat dilaksanakan dengan seadil-adilnya, sebab dengan mempelajari hukum kewarisan Islam maka bagi ummat Islam, akan dapat menunaikan hak-hak yang berkenaan dengan harta warisan setelah ditinggalkan oleh muwarris (pewaris) dan disampaikan kepada ahli waris yang berhak untuk menerimanya. Dengan demikian seseorang dapat terhindar dari dosa yakni tidak memakan harta orang yang bukan haknya, karena tidak ditunaikannya hukum Islam mengenai kewarisan. Pembagian harta waris dalam islam telah begitu jelas diatur dalam al qur an, yaitu pada surat an-Nisa. Allah dengan segala rahmat-Nya, telah memberikan pedoman dalam mengarahkan manusia dalam hal pembagian harta warisan. Pembagian harta ini pun bertujuan agar di antara manusia yang ditinggalkan tidak terjadi perselisihan dalam membagikan harta waris. Harta waris dibagikan jika memang orang yang meninggal meninggalkan harta yang berguna bagi orang lain. Aturan mengenai Perkawinan dan Mewaris yang diatur dalam Kitab Undang-undang Hukum Perdata (â€œKUHPerdataâ€), berlaku untuk golongan WNI Timur Asing Tionghoa, yang bukan beragama Islam. Dalam Pasal 852 KUHPerdata dinyatakan antara lain bahwa : Ahli waris adalah anak-anak atau sekalian keturunan mereka, biar dilahirkan dari lain-lain perkawinan sekalipun, mewaris dari kedua orang tua, kakek nenek atau semua keluarga sedarah mereka selanjutnya dalam garis lurus keatas dengan tiada perbedaan antara laki atau perempuan dan tiada perbedaan antara kelahiran lebih dahulu. Mereka mewaris kepala demi kepala jika dengan si meninggal mereka bertalian keluarga dalam derajat kesatu dan masing-masing mempunyai hak karena diri sendiri; mereka mewaris pancang demi pancang, jika sekalian mereka atau sekedar sebagian mereka bertindak sebagai pengganti. Dalam halnya mengenai warisan seorang suami atau istri yang meninggal terlebih dahulu, si istri atau suami yang hidup terlama dipersamakan dengan seorang anak yang sah dari yang meninggal. Berdasarkan ketentuan di atas berarti anak-anak keturunan berhak mewaris dari orang tua atau kakek-nenek dan keluarga sedarah dengan jumlah bagian yang sama. Begitu pula istri, memiliki hak dan besaran warisan seperti halnya anak sah.